Advancing social equity in urban tree planting: Lessons learned from an integrative review of the literature - Myers, Genevieve; Mullenbach, Lauren E.; Jolley, Julianna A.; Cutts, Bethany B.; Larson, Lincoln R. (Urban forestry & urban greening, 2023)
Social equity has become a growing emphasis in urban tree planting programs, with multiple cities across the world aiming to reduce racial/ethnic and socio-economic disparities in tree canopy distribution. However, despite escalating concerns about equity in urban greening, there is a dearth of research that applies the principles of environmental justice – including both recognition and procedural justice - to tree planting, specifically. This integrative review identified and analyzed academic papers focused on social and environmental justice related to urban tree planting programs in the United States. We searched academic databases using keywords such as “social equity AND tree planting” to identify peer-reviewed papers on the subject. After several filtering steps, 15 papers published between 2004 and 2021 were analyzed to understand outcomes from strategies that cities have employed in pursuit of equitable tree planting and the factors that influenced their success. We characterized outcomes, documented challenges faced, and identified best practices for equitable urban greening. Critical lessons learned include the value of prioritizing distributional equity over the number of trees planted, the need to form community partnerships and engage communities in the tree planting programs, and the importance of providing funding and resources for ongoing tree maintenance after initial planting. More research is needed to build on the limited studies to date with the goal of effectively integrating multiple environmental justice dimensions (i.e., distributive, procedural, recognition) into urban tree planting programs.